Problemática socioambiental urbana dos resíduos sólidos em Caririaçu-CE - Lucena, Cristiely Batista de (2025)
Solid waste has emerged as a significant challenge, especially in urban spaces, constituting a fundamental component in the study of the society-nature interface. As society modernized, techniques and tools were incorporated into the expropriation of nature, representing both a profound change in the landscape and an exponential increase in consumerism, resulting in a wide range of socio-environmental impacts. Given this scenario, this research aims to analyze the urban socio-environmental issues of solid waste in the small urban center of Caririaçu, Ceará. To this end, the following specific objectives were established: to characterize the physical and geographic attributes of the landfill's surroundings and the land use and occupation patterns, in order to understand how these activities contribute to the problem; to identify the predominant materials in solid waste and their local consequences; to evaluate the municipal government's actions in selecting the area designated for solid waste and its maintenance; and to analyze the municipality's urban structure, correlating it with urban growth toward the landfill area. In terms of methodological procedures, the research employed the hypothetical-deductive method to validate the central hypothesis, combining it with the geosystem approach, which allowed for a systemic analysis of the landscape. The study utilized bibliographic and documentary research, direct observation, fieldwork, data collection, and satellite imagery, enabling the development of cartographic representations, graphs, and tables for a better understanding of the physical and social elements. The theoretical basis for the research is based on studies on systemic landscape analysis and the socio environmental approach, which enabled an integrated understanding of the problem. The results demonstrated that the city of Caririaçu, Ceará, still does not adequately treat its urban solid waste, despite participating in the Cariri Integrated Solid Waste Management Consortium (CGIRS). One positive aspect is the closure of the open-air dump and the disposal of solid waste in a sanitary landfill in Juazeiro do Norte, a neighboring municipality. Ultimately, proper management of urban solid waste is a multifaceted challenge, requiring, above all, adjustments to the implementation of the National Solid Waste Policy (PNRS), especially in small municipalities.